2020
DOI: 10.1002/cpp.2532
|View full text |Cite
|
Sign up to set email alerts
|

Young people's narratives of hearing voices: Systemic influences and conceptual challenges

Abstract: Despite the prevalence of voice hearing in childhood and adolescence, little qualitative research has been undertaken with young people directly to advance phenomenological and aetiological insights into their experiences and interpretations.Consequently, the researchers sought demographic, contextual, and qualitative data from 74 young people from eleven countries, aged 13-18 years (28% = male; 61% = female; 21% = Transgender and Gender Non-Binary [TGNB]), who selfidentified as hearing voices. A Foucauldian-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 65 publications
(88 reference statements)
0
17
0
Order By: Relevance
“…This chimes with Morrison et al ( 2020 ) who highlighted that young people in first episode psychosis (FEP) services can be reluctant for family to be involved. However, in line with Parry et al ( 2021 ), family stories and influences had clearly been absorbed, even if they were not explicitly acknowledged. Supporters that were most valued were often parents that they did not live with, siblings, extended family and friends.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This chimes with Morrison et al ( 2020 ) who highlighted that young people in first episode psychosis (FEP) services can be reluctant for family to be involved. However, in line with Parry et al ( 2021 ), family stories and influences had clearly been absorbed, even if they were not explicitly acknowledged. Supporters that were most valued were often parents that they did not live with, siblings, extended family and friends.…”
Section: Discussionmentioning
confidence: 64%
“…Shame, secrets, and isolation are a common feature of voice‐hearing accounts (Woods, 2017 ) and these are no exception. Here they tangle together with cultural and systemic influences such as fear of judgement and stigma (Parry et al, 2021 ). The strongest common influence between parents and young people, though contested in different ways, was ‘voices = bad/mad’.…”
Section: Discussionmentioning
confidence: 99%
“…By using a nuanced first‐person perspective analysis of online survey data, Parry and Varese ( 2020 ) reported that distressing voices were mostly described with a sense of relational distance, which is consistent with adult literature (Hayward, 2003 ). Moreover, findings indicated that voices often reflected how young people experienced close social relationships, potentially showing an important role for the influence of appraisals of social others on young people's voice‐hearing experience and/or vice versa (Parry et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adult research has suggested that hearers could spend a substantial amount of time talking to voices, creating interpersonal relationships with them (Corstens et al, 2012 ) and that voices could be fulfilling social needs that are not met in other relationships (Beavan & Read, 2010 ; Corstens et al, 2012 ; Mawson et al, 2010 , 2011 ), potentially leading to spending less time in other social interactions (Favrod et al, 2004 ). Parry et al ( 2020 ) reported that young people commonly attributed their voice‐hearing to loneliness and social isolation. In turn, however, voices, irrespective of being positive or negative, could make social interactions more difficult as they can have a negative effect on concentration, leading to more social isolation and in some cases young people becoming more dependent upon their voices, as a result (Parry & Varese, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation